2015
DOI: 10.1111/bcp.12576
|View full text |Cite
|
Sign up to set email alerts
|

Methadone dose in heroin‐dependent patients: role of clinical factors, comedications, genetic polymorphisms and enzyme activity

Abstract: AIMSMethadone is characterized by wide intersubject variability regarding the dose needed to obtain full therapeutic response. We assessed the influence of sociodemographic, ethnic, clinical, metabolic and genotypic variables on methadone maintenance dose requirement in opioid-dependent responder patients. METHODSEighty-one stable patients (60 men and 21 women, 43.7 ± 8.1 years old, 63.1 ± 50.9 mg day À1 methadone), divided into quartiles with respect to the median daily dose, were enrolled and underwent clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 32 publications
3
63
0
Order By: Relevance
“…In our study, the frequency of the CYP2B6 516T allele was 29%, which is almost identical to that reported by Crettol et al or Mouly et al The frequency of CYP2D6 PMs was slightly higher than the expected 5–10% but was within expected population variation regarding Confidence interval . It has already been reported that CYP2D6 PM status has no influence on methadone plasma level …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, the frequency of the CYP2B6 516T allele was 29%, which is almost identical to that reported by Crettol et al or Mouly et al The frequency of CYP2D6 PMs was slightly higher than the expected 5–10% but was within expected population variation regarding Confidence interval . It has already been reported that CYP2D6 PM status has no influence on methadone plasma level …”
Section: Discussionsupporting
confidence: 91%
“…In our study, we did not observe this clinical adjustment; we observed that the TT group had a lower dose administered, and the GT group a higher dose administered. Surprisingly, similar results were reported in the Mouly et al study . However, both studies included a small number of subjects, and these results need to be confirmed in a larger cohort.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The correlation with earlier BMI may reflect the fact that patients' weight and height are just two of several factors that influence what constitutes an individual's adequate methadone dose [23][24]. It should be noted that a patient's methadone dose is determine by a physician, based mainly on clinical opioid withdrawal or intoxication signs and symptoms, as well as evidence of opioids in urine analyses, and only to a lesser extent on subjective reports of craving.…”
mentioning
confidence: 99%